Volatility, External Debt, and Fiscal Risk: Simulations of the Impact of Shocks on Fiscal Adjustment for Thirteen Latin American Countries - Kenneth Kletzer (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper examines how the combination of indebtedness and exogenous shocks induce volatility for the countries of Latin America. A techique for simulating the impact of shocks on the costs of external indebtedness and the response of fiscal policies in adjustment to such shocks is presented and applied to thirteen indebted Latin American countries.
Keywords: 330